ARTISTIC INTERPRETATION AND RESOLUTION OF HUMAN TRAGEDIES IN THE STORY - Saitov, Suxrob (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This article presents scientific conclusions about the story genre, its characteristics, artistic interpretation and solutions of human tragedies reflected in the story. Also, the importance of the story in describing the emotional experiences of a person is proven by the opinions of literary experts.